2015
DOI: 10.1063/1.4923181
|View full text |Cite
|
Sign up to set email alerts
|

Non-adiabatic current densities, transitions, and power absorbed by a molecule in a time-dependent electromagnetic field

Abstract: The energy of a molecule subject to a time-dependent perturbation separates completely into adiabatic and non-adiabatic terms, where the adiabatic term reflects the adjustment of the ground state to the perturbation, while the non-adiabatic term accounts for the transition energy [A. Mandal and K. L. C. Hunt, J. Chem. Phys. 137, 164109 (2012)]. For a molecule perturbed by a time-dependent electromagnetic field, in this work, we show that the expectation value of the power absorbed by the molecule is equal to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…The evaluation of the currents implies the evaluation of the exact Dyson equation (37) following the methods of [66,67]. A similar situation was analyzed in [91], where it was found that the rate of change for the nonadiabatic energy agrees with the work done on a molecule subjected to a time-dependent applied field. The work in [92] discusses heat transfer across a triple dot structure with the nonadiabatic driving applied to an edge dot.…”
Section: Nonadiabatic Regimementioning
confidence: 86%
“…The evaluation of the currents implies the evaluation of the exact Dyson equation (37) following the methods of [66,67]. A similar situation was analyzed in [91], where it was found that the rate of change for the nonadiabatic energy agrees with the work done on a molecule subjected to a time-dependent applied field. The work in [92] discusses heat transfer across a triple dot structure with the nonadiabatic driving applied to an edge dot.…”
Section: Nonadiabatic Regimementioning
confidence: 86%
“…The non-local response functions allow us to exactly calculate heterodyne detected optical signals in the presence of strong fields and non-uniform nano optical fields 12,38 . The formalism can be used to study non-adiabatic molecular current density dynamics 39 . Furthermore, it can be extended to cavity quantum electrodynamics (QED), or be used in understanding field angular momentum 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the fact that, in quantum mechanics, the interaction between charges and electromagnetic fields can be written in terms of the scalar-vector potential ( A 0 ( r ), A ( r )), which changes under gauge transformation, whereas all observables must be gauge invariant. 10 This makes the problem of nonlocal optical response rather involved.…”
Section: The Chiral Non-local Response Functionsmentioning
confidence: 99%